A risk map methodology to assess the spatial and temporal distribution of leakage into groundwater from Geologic Carbon Storage. (April 2017) - Siirila-Woodburn, Erica R.; Cihan, Abdullah; Birkholzer, Jens T.
Highlights: A new methodology is presented to generate GCS spatial "risk maps". Leakage risk into groundwater defined with no-impact or MCL thresholds. Probability theory and analytical/numerical methods are computationally inexpensive. An hypothetical example of a fully-coupled system demonstrates the methodology. Abstract: The risks to potable aquifers due to brine leakage through plugged and abandoned (P&A) wells is highly uncertain and a potentially significant contributor to the risk profile in Geologic Carbon Storage (GCS). This uncertainty stems from the unknown location of wells and the large variance of P&A wellbore permeability, making the spatial assessment of P&A brine leakage risk challenging. A new methodology is presented to generate "risk maps", or spatial distributions of brine leakage risk to groundwater resources as defined with no-impact or Maximum Contaminant Level (MCL) thresholds. The methodology utilizes probability theory, thereby avoiding the use of computationally expensive Monte Carlo simulations while maintaining flexibility in modeling techniques. These maps provide quantitative probabilities of risk as a function of time to inform site selection and monitoring during and post-injection, conducive to the US EPA's permitting of class-VI wells and the so-called "area of review", AoR. As a demonstration of the methodology, a numerical model of a hypothetical fully-coupled system spanning from the injection reservoir to the USDW is used to assess the evolution of brine leakage through P&A wells. Risk maps of CO2 leakage can also be generated with this methodology for a comprehensive assessment of GCS leakage risk.